Edukasi Peningkatan Kualitas Pencatatan Data di Posyandu Bougenville 1 Kota Jambi - Adinda Novita; Syauqina Ahza Magfira; Willia Novita Eka Rini; Al Qohiyulan Tiar; Dwi Amelia; Muthiah Fauziyyah Syadiq; Rangi Media Pebriza (PPNI UNIMMAN, 2025)
Posyandu Bougenville 1 is a self-help activity that aims to maintain and maintain public health, especially for pregnant women and toddlers. Until now, data recording at Posyandu Bougenville 1 is still manual so that data can be written incomplete, incorrectly inputted, or difficult to read, potentially causing inaccuracies in reporting and taking longer to recapitulate and report, which can hamper decision making. The purpose of this activity is to increase cadres' awareness of the importance of NCD surveillance, measure NCD risk factors in vulnerable groups, and increase community knowledge about NCD prevention efforts, as well as introduce the E-PPGBM application in general. This study was conducted using a descriptive qualitative approach using interviews with two posyandu cadres and participatory observation of Posyandu Bougenvile 1 cadres. The education provided to cadres was proven to increase their understanding of the importance of accurate and systematic data recording, and encourage them to be more active in monitoring community health.